Management of Zygomatic Fractures: A National Survey. Issue 6 (September 2016) - Baylan, Joseph M.; Jupiter, Daniel; Parker, Wendy L.; Czerwinski, Marcin
Abstract : Introduction: Repair of zygomatic fractures can be classified into the early closed reduction or the more recent open reduction and rigid internal fixation (ORIF) methods. Surgical training and literature advocate ORIF, but the actual frequency of the different techniques in clinical practice is unknown. The purpose of this study was to determine the current trends in the management of zygomatic fractures among US surgeons and elucidate their influences. Methods: A 10-question survey was developed and distributed to over 16, 000 practicing US facial trauma surgeons, including plastic surgeons (PS), oral and maxillofacial surgeons (OMFS), and otorhinolaryngologists (ENT). The survey queried training background, zygoma fracture treatment preferences, and rationale. Responses were tabulated and both univariate and bivariate statistical analyses completed. Results: One thousand six hundred eleven (10%) total responses were received. Zygomatic fractures are treated most commonly by OMFS (61%), then PS (20%) and ENT (19%), with 71% of repairs being performed in private practice. Open reduction and rigid internal fixation is the most common treatment modality (81%), with most surgeons using 2 to 3 sites for exposure, reduction, and fixation with titanium miniplates (70%). Thirty-five percent of surgeons perform routine orbital floor exploration. Forty-three percent quoted training and 32% reported accuracy of repair as the primary reason for choosing ORIF. Conclusions: This is the largest reported survey on the repair of zygoma fractures. The response rate suggests dominance of OMFS in zygoma fracture care, an area pioneered by PS. Evolution of technique is also evident by predominance of ORIF with emphasis of multiple points of exposure, reduction, and fixation with rigid hardware.